Serum levels of sFas and sFasL during chemotherapy of lung cancer - Naumnik, W.; Iżycki, T.; Ossolińska, M.; Chyczewska, E. (Experimental Oncology, 2007)
The aim of this study was to assess the clinical usefulness of determination of soluble Fas (sFas) and soluble Fas Ligand (sFasL) during chemotherapy of lung cancer. Methods: The study included 80 patients (69 males; 11 females; mean age 64 years; 48 with non-small cell lung cancer-NSCLC, 32 with small cell lung cancer-SCLC). The control group consisted of 15 healthy volunteers. The peripheral blood samples were taken before and after 4 cycles of chemotherapy. sFas and sFasL levels were assessed by Elisa method. Results: The serum sFas and sFasL levels observed at the end of the chemotherapy were higher in all patients with lung cancer compared to healthy volunteers. The levels of sFas and sFasL were higher after chemotherapy than before therapy. The levels of sFasL were significantly higher in SCLC patients than in NSCLC ones. There were no significant differences in serum sFasL levels in relation to clinical stage of lung cancer. After chemotherapy the levels of sFas were higher in patients with metastases. There were no significant differences in serum sFasL levels in relation to response to therapy. At the end of the therapy the serum levels of sFas were higher in Partial Response group than in Progressed patients. Before chemotherapy the levels of sFas were higher in Progressive Disease group than in No Change one. The levels of sFas observed after chemotherapy were higher in Partial Response group than in No Change one. Conclusion: Determination of serum sFas and sFasL levels can be useful in clinical practice, but their practical significance needs further studies. Цель работы —оценить клиническую целесообразность определения уровня растворимого Fas (sFas) и растворимого лиганда Fas (sFasL) в сыворотке кровибольных раком легкого при химиотерапии. Методы: обследовали 80 пациентов (69 мужчин и 11 женщин; средний возраст — 64 года; из них у 48 диагностирован немелкоклеточный рак легкого (НМКРЛ), у 32 — мелкоклеточный рак легкого (МКРЛ)). Контрольная группа состояла из 15 здоровых доноров. Образцы периферической крови брали до и после 4 курсов химиотерапии. Содержание sFas и sFasL ана лизировали иммунофер ментным методом. Результаты: уровни sFas и sFasLв сыворотке крови всех больных раком легк ого по окончании хими отерапии выше, чем таковые в контрольной группе и чем таковые до терапии. Уровень sFasL был значительно выше у больных МКРЛ, чем таковой у пациентов с НМКРЛ. Значительных различий в уровне sFasLв сыворотке крови в за висимости от клинической стадии заболевания не выявлено. По окончании химиотерапии уровень sFas выше у пациен тов с метастазами, а также в группе с частичным ответом на терапию, чем у больных с прогрессирующим заболеванием. До начала терапии уровень sFas был выше у больных с прогр ессирующим забо лева нием, чем у па циентов со стабильным состоянием , а по окончании терапии – у больных с частичным ответом по сравнению с группой больных со стабильным состоянием. Выводы: определение уровня sFas и sFasLв сыворотке крови может быть пр именено в клинической практике, но зна чимость та ких показателей необходимо определить в дальнейших исследованиях.